Implementation Of Intervention Program For Controlling Glucose Level Among ICU Patients - Al-Haqeesh, Hiyam; Alhuneity, Shereen Ziad; Obeidat, Laith A; Al Rashaydah, Ali Sayel; Albedoor, Jebril Ahmed; Abeeleh, Jaafar Abu; AlKhatib, Ahed J; Alhawari, Husam; Abu Abeeleh, Mahmoud A (European Scientific Journal, ESJ, 2016)
Introduction: Hyperglycemia and insulin resistance are common in critically ill patients, even if they have not previously had diabetes, and the risk of mortality or significant morbidity is high among those who are treated in the intensive care unit (ICU) for more than 5 days. Study objectives: To assess the effect of glucose management protocol on mortality and morbidity in a heterogeneous population of critically ill adult patients. Methods and materials: Study design: A randomized controlled trial. Study setting: Intensive care unit (ICU) for adult patients at King Hussein Medical Center, the Royal Medical Services. Study sample: A total of 50 patients were included in this study and assigned randomly into two groups, control group (N=25), and intervention group (N=25). Study protocol: The intervention group subjects were to undergo a glucose control protocol with insulin infusion titrated to maintain blood glucose level in a target range of 120-160 mg/dL; except septic patients, in whom the target was higher, 160- 180 mg/dL. Patients in the second group (control group) were treated by a conventional approach with reduction of blood glucose level only if the level was markedly elevated (>200 mg/dL) to maintain blood glucose level in a target range of 180-200 mg/dL Study findings: Although the difference in mortality between the two treatment groups was not significant at 28 days (p=0.370) and at 60 days (p=0.555), but it was to be considered for further improvements. No significant increase in hypoglycemia episodes was reported in our blood glucose level target. There was no significant difference in the development of new organ failure, new renal insufficiency, number of patients undergoing transfusion of packed red blood cells, use of antibiotics for more than 10 days, length of stay in the ICU and length of stay in the hospital. It was noticed that the rates of positive blood cultures were lower in the interventional group (8%) than in the control group (32), (p=0.068). Conclusion: The glucose management protocol resulted in significantly improved glycemic control and was not associated with increased rate of death or hypoglycemia.